THE INFLUENCE OF FITRAT’S WORKS ON MODERN LITERATURE AND SOCIETY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article highlights how Abdurauf Fitrat passionately devoted himself to the intellectual and moral development of Uzbek youth and the nation as a whole. Each of his works, imbued with a new spirit and unique fervor, serves as a truthful conduit that reaches readers’ hearts and minds.